Instrumenting the Dynamic Web - Edmonds, Andy; White, Ryen W.; Morris, Dan; Drucker, Steven M. (Journal of Web Engineering, 2007)
One of the most critical driving forces in the evolution of interfaces on the Internet has been the logging built into common Web servers and the decade-long deployment of analytics based upon this data source. Page-view logging has slowly moved to callback systems using client-side scripting to capture more aspects of the user experience. With the rise of JavaScript-based client-side interactivity and, more recently, asynchronous Javascript and XML (AJAX), server-side logging is less able to capture the user experience of Web sites and applications that are rising in complexity. We present a new technique for the in-page logging of interaction events that will help interaction designers make more informed design decisions based on how users are interacting with their systems. The potential benefit of our technique is demonstrated in a case study with a working system.